2020
DOI: 10.1111/ajr.12593
|View full text |Cite
|
Sign up to set email alerts
|

Access and outcomes of general practitioner obstetrician (rural generalist)‐supported birthing units in Queensland

Abstract: Objective To describe characteristics and outcomes of women birthing within GP‐obstetrician (rural generalist) supported rural (level 3) obstetric units in Queensland. Design Retrospective descriptive study. Setting 21 GP‐obstetrician supported birthing units in Queensland. Participants Women (n = 3111) birthing from January 2017 to December 2017. Main outcome measures Patient, pregnancy and labour characteristics and key maternal and neonatal outcomes routinely recorded in the Queensland Perinatal Data Collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…However, outside of general practice, significant gaps remain in specialist training pipelines outside of metropolitan areas 21 . In Queensland, the establishment of rural generalist training has been successful in improving access to services traditionally delivered by non‐GP specialists 22 . The broader expansion of the rural generalist model could achieve similar outcomes in other jurisdictions 23 ; however, coordination is needed to ensure structural, policy and industrial conditions support rural generalist models of training and service delivery 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, outside of general practice, significant gaps remain in specialist training pipelines outside of metropolitan areas 21 . In Queensland, the establishment of rural generalist training has been successful in improving access to services traditionally delivered by non‐GP specialists 22 . The broader expansion of the rural generalist model could achieve similar outcomes in other jurisdictions 23 ; however, coordination is needed to ensure structural, policy and industrial conditions support rural generalist models of training and service delivery 21 .…”
Section: Discussionmentioning
confidence: 99%
“…21 In Queensland, the establishment of rural generalist training has been successful in improving access to services traditionally delivered by non-GP specialists. 22 The broader expansion of the rural generalist model could achieve similar outcomes in other jurisdictions 23 ; however, coordination is needed to ensure structural, policy and industrial conditions support rural generalist models of training and service delivery. 21 Strengthening collaboration between training organisations in rural and remote areas could increase capacity and reduce the gaps in vocational training pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Queensland-based study demonstrated that GPO-supported birthing units had strong indicators of quality and safety. 5 The National Rural Generalist Taskforce recognise the importance of supporting and valuing of rural generalists, including…”
Section: General Practitioner Obstetricians' Models Of Care In Rural ...mentioning
confidence: 99%
“…There has been little academic attention paid to the role of GPs or GPOs on outcomes in maternity care. A recent Queensland‐based study demonstrated that GPO‐supported birthing units had strong indicators of quality and safety 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation